THE ROLE OF YOUTH IN THE DEVELOPMENT OF SRIWIJAYA VILLAGE IN KUALA SIMPANG DISTRICT, ACEH TAMIANG DISTRICT, ACEH PROVINCE - Ahmad Nubli Gadeng; Dwi Aqni Julian; Sanusi Sanusi; Ruliani Ruliani; Mice Putri Afriyani; Ade Fitria; Ramli Ramli; Daska Azis (GeoEco, 2025)
The goal of this study was to find out what part young people play in the growth of Sriwijaya Village in Aceh Tamiang Regency. The study method used is descriptive qualitative, and interviews and written records were used to collect data. Data analysis uses techniques for reducing the amount of data, showing the data, and checking and confirming the findings. The study's results are: 1) The young people of Sriwijaya Village are active, getting other people in the community to take part in planning for the village's future and making decisions about it. 2) The young people of Sriwijaya Village are a source of motivation. This is clear from the fact that they are active in youth groups that encourage other people to work together and help keep the village safe. The young people of Sriwijaya Village are creative and come up with new ideas. For example, they have started online conversation groups about planning for village development and organize sports events for positive youth activities in planning for regional development. 4) The young people of Sriwijaya Village are a driving force. First, they figure out what the problems are in Sriwijaya Village, and then they plan activities to fix them, like leadership training and activities. Lastly, the young people of Sriwijaya Village do a lot to help the village grow. Because Sriwijaya Village's future growth or decline will depend a lot on how well today's kids deal with things.